Comprehensive Review of Environmental Health Factors, Healthcare Access, and Policy Reform - Alabbas, Hamad Ali Hossin; Albalhareth, Gahdeer Hadi Sale; Alalhareth, Mohammed Saleh Salem; Alqisi, Seham Ali Ahmed; Alqashanin, Nasser Mahdi Nasser; Almansour, Abdulrahman Huwaydir Saeed; Al saed, Mohsen Mohammed Nasser; shahi, Ali Hamad Ali; Alalhareth, Abdullah Nasser Saleh; al kolip, Saleh mana saleh; Al Suleiman, Mohammad Rajeh Mohammad (Journal of Ecohumanism, 2024)
Several environmental health issues, together with access to healthcare and health policy, are inextricably connected to shaping the health of nations. Pollution, climate change, and poor housing and living standards are reasons health risks vary from one population group to another. Equally important, the use of healthcare services depends on socio-economic characteristics, regional location, and healthcare system performance. Health policy changes are fundamental to increasing access to health care and eradicating the causes of health-related issues in the environment. The present review aims to review the interaction between environmental factors and accessibility to health care and the outcome of health due to policy interventions. It explains why people have limited healthcare access and healthcare disparities among disadvantaged populations and what it says are systemic policy changes required to achieve healthy equity. The study shows that effective interventions in social determinants for health and developing policies on sustainable environmental use are necessary to improve people’s health worldwide.